Characteristics of foreign-owned firms in British manufacturing - Rachel Griffith; Helen Simpson (Institute for Fiscal Studies (IFS), 2001)
This paper describes the characteristics of manufacturing establishments in Britain over the period 1980 to 1996. Particular attention is paid to differences between plants of different ownership nationality. The findings suggest that establishments that are always foreign-owned have significantly higher labour productivity than those that remain under domestic ownership. In addition, labour productivity improves faster over time and faster with age in foreign-owned establishments. The difference in labour productivity is matched by an equivalent difference in levels of investment per employee. Establishments that change ownership nationality do not seem to experience very large changes in labour productivity levels. The proportion of skilled workers in the workplace, and wages for both skilled and operative workers are higher in foreign-owned establishments than domestic-owned, in line with differences in labour productivity.
Keywords: 330; foreign direct investment; productivity; multinational firms; Direktinvestition; Verarbeitendes Gewerbe; Multinationales Unternehmen; Arbeitsproduktivität; Großbritannien